The Affecting Factors of Nurse Fatigue in The ICU and ER of Bhayangkara HS. Samsoeri Mertojoso Hospital - Bagus Tejo Purnomo (Universitas Airlangga, 2020)
Introduction: Nurses have a very stressful job because they are required to deal with the needs of patients. Nurses are responsible for contacting and observing patients 24 hours a day. The nurse fatigue is associated with stress at work, workload, and the level of conflicts that occurs in the work environment. This research aims to analyze the relationship between the individual characteristics and fatigue of nurses’ performance in the ICU and ER. Methods: This research is observational research with a cross-sectional design and the analysis used in this study is a descriptive analysis conducted in the form of frequency tables and cross tabulations. The research data were obtained from filling in identity data sheets, IFRS work fatigue measurement questionnaires, and calorimeter measurements. To analyze the relationship between two variables with ordinal and nominal data scales including non-parametric statistics and due to the total population in this study, to find out how strong the relationship value is the Cramer V value in the Chi Square Test. The sample used was 25 nurses who work in the ICU and ER. Results: There is a relationship on the characteristics of nurses in the study which includes age, sex, length of service, education level, marital status, nutritional status, length of work, workload with subjective fatigue in ICU and ER nurses. Conclusion: In the test results obtained varying results from strong to weak relationship. In conclusion, individual characteristics cause subjective fatigue in ICU and ER nurses.Keywords: emergency room, intensive care unit, nurses, subjective fatigue